The music shop : a novel - Joyce, Rachel (Random House, 2018)
"A love story and a journey through music, the exquisite and perfectly pitched new novel from the bestselling author of The Unlikely Pilgrimage of Harold Fry and The Love Song of Miss Queenie Hennessy"--